2011
DOI: 10.1007/s11270-011-0815-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Amendments to Control Phosphorus Losses in Runoff from Dairy-Soiled Water

Abstract: Amendments with the potential to reduce phosphorus (P) losses from agricultural grassland arising from the land application of dairy-soiled water (DSW) were investigated. Optimal application rates were studied, and associated costs and feasibility were estimated. First, batch tests were carried out to identify appropriate chemicals or phosphorus sorbing materials to control P in runoff from DSW. Then, the best four treatments were examined in an agitator test. In this test, soil-placed in a beaker-was loaded w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 19 publications
(23 reference statements)
0
13
0
Order By: Relevance
“…For example, Moore and Edwards (2007) monitored two catchments since 1995 and found that, in one with poultry litter applied, much more P (1.5 kg P ha −1 yr −1 ) was lost than from an adjacent catchment with applied poultry litter amended with alum (0.45 kg P ha −1 yr −1 ). Recent research in Ireland has shown that mixing alum with dairy‐soiled water (e.g., dairy shed effluent) or pig slurry can decrease concentrations and loads of FRP, TP, ammoniacal‐nitrogen, and suspended solids in runoff generated by rainfall simulation onto ungrazed grassland (Brennan et al, 2011, 2012; Fenton et al, 2011; O'Flynn et al, 2012, 2013; Serrenho et al, 2012). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Moore and Edwards (2007) monitored two catchments since 1995 and found that, in one with poultry litter applied, much more P (1.5 kg P ha −1 yr −1 ) was lost than from an adjacent catchment with applied poultry litter amended with alum (0.45 kg P ha −1 yr −1 ). Recent research in Ireland has shown that mixing alum with dairy‐soiled water (e.g., dairy shed effluent) or pig slurry can decrease concentrations and loads of FRP, TP, ammoniacal‐nitrogen, and suspended solids in runoff generated by rainfall simulation onto ungrazed grassland (Brennan et al, 2011, 2012; Fenton et al, 2011; O'Flynn et al, 2012, 2013; Serrenho et al, 2012). …”
Section: Resultsmentioning
confidence: 99%
“…The least significant difference at the 5% level is given for the comparison of all treatments before and after application and between alum treatments after alum had been applied. ammoniacal-nitrogen, and suspended solids in runoff generated by rainfall simulation onto ungrazed grassland (Brennan et al, 2011(Brennan et al, , 2012Fenton et al, 2011;O'Flynn et al, 2012O'Flynn et al, , 2013Serrenho et al, 2012).…”
Section: Potential For Managementmentioning
confidence: 99%
“…Other studies (Brennan et al 2011;Fenton et al 2011;O' Flynn et al 2011) have used a combination of batch experiments, agitator experiments and runoff box experiments (together with isotherm parameterisation) to ascertain application rates and effectiveness of amendments when added to animal manures. The feasibility of amendments in such studies was based on cost of application, pollution swapping potential and changes to the soil or slurry caused by amendment, e.g.…”
Section: Metal Mobilisation During Batch Experimentsmentioning
confidence: 99%
“…One way of immobilising this P before discharge to a surface waterbody is to amend soil in a riparian zone with a material that has a high P sequestration capacity. Iron-rich materials have been used to sequester P from wastewater (Gallimore et al 1999;Elliott et al 2002;Rhoton and Bigham 2005;Johansson-Westholm 2006;Brennan et al 2011;Fenton et al 2011). The capacity of ochre to sequester P from agricultural and municipal wastewater has previously been investigated for ochre from coal mining areas of the UK (Bozika 2001;Heal et al 2005;Dobbie et al 2009), the USA (Sibrell et al 2009) and metal mining areas of south east Ireland (Fenton et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation